Natural history of non-neovascular pigment epithelial detachments (PEDs): Comparison between serous and drusenoid PEDs - Mathilde M. Goudot; Eric H. Souied; Donato Colantuono; Camille Jung; Carl-Joe Mehanna; Benjamin Memmi; Giuseppe Querques; Salomon-Yves Cohen; Alexandra Miere (AJO International)
Purpose: To describe the long-term natural history of non-neovascular pigment epithelial detachments (nnPEDs), by comparing the multimodal imaging features of either serous or drusenoid PEDs (SPED and DPED) in patients with age-related macular degeneration. Methods: Eyes with nnPEDs > 700 μm in width and a height > 150 μm on spectral domain optical coherence tomography (SD-OCT), with at least 12 months follow-up, were included. SPED and DPED were distinguished. SD-OCT qualitative and quantitative variables were compared at baseline, at the time of maximal PED height, and at the final visit. Results: Forty-seven eyes of 31 patients were followed for 69 ± 35 months (mean age 68 ± 7.2 years): 27 eyes in the DPED group and 20 eyes in the SPED group. SPEDs were significantly higher and wider than DPEDs at the maximal PED height visit (p = 0.007 and p = 0.023, respectively). More apertures (p = 0.007), i.e., sharply demarcated discontinuities of the PED, and lateral subretinal fluid (p = 0.008) were observed in SPEDs. There was no significant difference between the two groups in the qualitative analysis or in the evolution over time. Ten eyes (50 %) with SPEDs and 11 eyes (41 %) with DPEDs (p = 0.46) progressed toward geographic atrophy, and 4 eyes (20 %) with SPEDs and 3 eyes (11 %) with DPEDs (p = 0.68) progressed toward fibrosis. Conclusion: This analysis of large nnPEDs revealed that large PEDs pose a high risk of complications regardless of their nature.